The tridecaptins: non-ribosomal peptides that selectively target Gram-negative bacteria. Issue 4 (22nd January 2021) - Bann, Samantha J.; Ballantine, Ross D.; Cochrane, Stephen A.
Abstract : Tridecaptins are a re-emerging class of non-ribosomal antibacterial peptides (NRAPs) with potent activity against highly problematic strains of Gram-negative bacteria. Abstract : Tridecaptins are a re-emerging class of non-ribosomal antibacterial peptides (NRAPs) with potent activity against highly problematic strains of Gram-negative bacteria. An intricate mode of action has been reported to explain the bactericidal activity of these NRAPs, wherein they bind selectivity to the Gram-negative version of the peptidoglycan precursor lipid II on the outer leaflet of the inner membrane and disrupt the proton-motive force. Tridecaptins are highly amenable to synthetic modification owing to their linear structure, therefore, various synthetic analogues have been reported, several of which have enhanced antimicrobial activity, reduced cost of synthesis and/or improved stability towards d -peptidase mediated hydrolysis. It has also been demonstrated that unacylated tridecaptins can act synergistically with clinically relevant antibiotics by sensitizing the outer membrane. This review will summarize past literature on the development/discovery of novel tridecaptin analogues (up until the end of 2020), some of which may be useful therapeutic agents to treat insidious Gram-negative bacterial infections.